Coeliac disease associated with congenital heart disease. - Congdon, P. J. (BMJ Group, 1982)
Six children with congenital heart disease are described in whom poor growth was found to be due to small-bowel villous atrophy; none was in heart failure and only one was severely cyanosed. Growth improved in all 6 on a gluten-free diet. Gluten enteropathy may be more common than is realised in children with congenital heart disease, and jejunal biopsy should be undertaken early in any patient with poor growth and no heart failure to exclude the coexistence of the condition.